2011
DOI: 10.1253/circj.cj-10-1278
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Anatomical Properties of a Myocardial Bridge in Coronary Heart Disease

Abstract: he myocardial bridge (MB) is an anatomical variant that often covers part of the left anterior descending coronary artery (LAD). 1 It occurs almost exclusively in the mid-portion of the LAD (Figure 1). 2,3 Muscular contraction of the MB itself alters blood flow within the LAD, as demonstrated by coronary angiography, and influences the distribution of hemodynamic stress. [3][4][5] It is widely accepted that an MB sometimes causes coronary heart disease (CHD), 2,5,6 either from direct compression of the MB at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1
22

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 81 publications
5
81
1
22
Order By: Relevance
“…In particular, the sample size was not large enough to deny the possible correlations between anatomic MB properties and proximal atherosclerotic plaque burden. Second, the rate of MB appears higher in the current study compared with past angiographic reports (prevalence 0.4–16%) in the literature 20. This might be attributed to the higher image resolution of IVUS and its ability to directly visualize MB muscle or may suggest that MB itself is a substantial contributor to anginal symptoms without obstructive coronary artery disease.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In particular, the sample size was not large enough to deny the possible correlations between anatomic MB properties and proximal atherosclerotic plaque burden. Second, the rate of MB appears higher in the current study compared with past angiographic reports (prevalence 0.4–16%) in the literature 20. This might be attributed to the higher image resolution of IVUS and its ability to directly visualize MB muscle or may suggest that MB itself is a substantial contributor to anginal symptoms without obstructive coronary artery disease.…”
Section: Discussioncontrasting
confidence: 68%
“…Another study using a catheter‐based pressure measurement system demonstrated that the intracoronary pressure within the LAD segment proximal to the MB was significantly higher than the aortic blood pressure, suggesting potential augmentation of the intimal injury at this segment 9. Finally, solid mechanical forces that result from the motion and deformation of the coronary tree and myocardial material properties may lead to a heterogeneous stress field at this segment 6, 9, 20, 21…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between MB anomaly and increased cardiovascular morbidity is still unclear. According to previous reports [21,30], the MB may cause coronary heart disease by two mechanisms. First, by a direct systolic compression of the tunnelled segment and second by the enhanced atherosclerotic plaque formation occurring because of alteration of haemodynamic factors, mainly in the vessel segment proximal to the bridge.…”
Section: Discussionmentioning
confidence: 93%
“…First, by a direct systolic compression of the tunnelled segment and second by the enhanced atherosclerotic plaque formation occurring because of alteration of haemodynamic factors, mainly in the vessel segment proximal to the bridge. The length, the depth and the location of the MB have been associated with the mechanisms above [21,30]. Therefore, MB is classified as superficial or deep, depending on the thickness of the covering muscular layer (≤ 1 mm or > 1 mm) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Biz bu çalışmamızda, koroner anjiografi yapılan hastalardaki MB prevalansını araştırmayı amaçladık. (20). Nadir olarakta sağ koroner arter ve Cx arterde de görülebilmektedir.…”
Section: Introductionunclassified